Being parents with epilepsy: thoughts on its consequences and difficulties affecting their children - Gauffin H (Dove Medical Press, 2015)
Helena Gauffin,1 Gullvi Flensner,2 Anne-Marie Landtblom1,3 1Department of Neurology and Department of Clinical and Experimental Medicine, Linköping University, Linköping, Sweden; 2Department of Nursing, Health and Culture, University West, Trollhättan, Sweden; 3Department of Neuroscience, Uppsala University, Uppsala, Sweden Objective: Parents with epilepsy can be concerned about the consequences of epilepsy affecting their children. The aim of this paper is to describe aspects of what it means being a parent having epilepsy, focusing the parents’ perspectives and their thoughts on having children.Methods: Fourteen adults aged 18–35 years with epilepsy and subjective memory decline took part in focus-group interviews. The interviews were conducted according to a semi-structured guideline. Material containing aspects of parenthood was extracted from the original interviews and a secondary analysis was done according to a content-analysis guideline. Interviews with two parents for the Swedish book Leva med epilepsi [To live with epilepsy] by AM Landtblom (Stockholm: Bilda ide; 2009) were analyzed according to the same method.Results: Four themes emerged: (1) a persistent feeling of insecurity, since a seizure can occur at any time and the child could be hurt; (2) a feeling of inadequacy – of not being able to take full responsibility for one’s child; (3) acknowledgment that one’s children are forced to take more responsibility than other children do; and (4) a feeling of guilt – of not being able to fulfill one’s expectations of being the parent one would like to be.Conclusion: The parents with epilepsy are deeply concerned about how epilepsy affects the lives of their children. These parents are always aware that a seizure may occur and reflect on how this can affect their child. They try to foresee possible dangerous situations and prevent them. These parents were sad that they could not always take full responsibility for their child and could not live up to their own expectations of parenthood. Supportive programs may be of importance since fear for the safety of the child increases the psychosocial burden of epilepsy. There were also a few parents who did not acknowledge the safety issue of their child – the authors believe that it is important to identify these parents and provide extra information and support to them. Keywords: focus group interviews, qualitative research, secondary analysis, guilt, feeling of inadequacy, insecurity